Cooperation of Uzbekistan in Sphere Art with Foreign Countries - Orifjon Nurmukhammadovich , Mirzaev (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses Uzbekistan’s cooperation with foreign countries in the field of art and youth participation. It also analyzes the stages of development of applied arts, fine arts, and photography and considers important aspects of international exhibitions.